The evolution from sector-specific regulation towards competition law in EU telecom markets from 1997 to 2011: Different effects in practical implementation - Natascha Freund; Ernst-Olav Ruhle (International Telecommunications Society (ITS), 2011)
The telecommunications markets in the European Union have gone through a period of rapid technological as well as economic change. After the market opening in the late 1990s, the approach to regulate these markets has likewise changed over time. Whereas a sectorspecific framework dominated the phase from 1998-2002, a more prominent role of competition law regulating telecommunications markets has become visible within the last years. The two reviews of the regulatory framework (2002 and 2010) have seen sector-specific measures being scaled back and competition law measures gaining a more prominent role. This paper tries to analyse the development from sector-specific regulation towards competition law in its application to telecommunications markets in the EU. It draws conclusions from the changes in the different reviews and demonstrates how these modifications of the framework have taken place. Additionally, the practical implementations are analysed with respect to two countries. Despite the fact, that EU member states are following a joint approach (EU framework), there are still differences on the national level as regards the application of regulatory instruments and the regulation of specific markets. This can be demonstrated by looking at how national regulatory authorities conduct the process of for example market definition, market analysis, SMP designation and levying of remedies. In the paper Germany and Austria are analysed, two neighbouring countries, with similar principles in the transposition of EU frameworks into national legislation, but with strongly different outcomes as regards specific regulatory measures in terms of e.g. market analysis, price regulation, organisation of the regulatory authorities etc. Thereby we demonstrate that although the EU framework tends to achieve harmonisation, there are still a number of differences between member states in practical implementation. The paper is organised as follows: after the introduction in section 1, section 2 draws the picture of the development of the most important elements of the EU regulatory framework over time. Thereby. we specifically look at the issues of market definition, analysis and dominance designation but also issues of access and interconnection are analyzed. This encompasses conclusions regarding the overall trends of development in the design of the EU regulatory framework. Section 3 analyses the corresponding developments in the Austrian and the German telecommunications act, especially with respect to the balance between the role of sector-specific regulation and competition law in national legislation. This is done be looking at some specific topics such as, market definition and analysis, organization of the regulatory authority, potential conflicts between regulatory authority and competition authority regarding competences and responsibilities, possibilities of enforcement, and the treatment of margin squeeze. Section 4 contains our conclusions with respect to the practical implementation in member states against the overall goal of harmonisation and demonstrates differences in the way EU legislation has been transposed to national legislation in a comparison between Germany and Austria.
Keywords: 330